SOCIAL INTERACTION, INFORMATION SHARING, AND BRAND TRUST IN OPTIMIZING PURCHASE INTENTION BASED ON THE THEORY OF PLANNED BEHAVIOUR - Rahma, Atika (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
Social interaction is a key variable in this research. Previous studies have identified gaps that require further investigation. The findings provide valuable insights for companies developing effective marketing strategies by leveraging social interactions and information sharing to enhance brand trust and increase purchase intention. This research focuses on Bandung, Surabaya, Semarang, Yogyakarta, Lampung and Medan as these cities have the highest usage of cosmetic products. A purposive sampling technique was used, selecting 145 respondents from generations Y and Z who are active cosmetic users. This research adopts a quantitative approach, with data analysis conducted using SPSS 29 and Amos Graphic 26 software. Unlike previous studies. This research introduces brand trust as a variable. The findings reveal that brand trust does not significantly influence purchase intention. Consumers who perceive that cosmetic products do not offer benefits proportional to their high prices are less likely to let brand trust affect their purchase intentions. JEL: M31, M21, L84.